Akhlak Tasawuf - Happy Syafaat Sidiq (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Sufism morals are increasingly needed in the current era to minimize the evils and gaps in human attitudes towards themselves, fellow humans and also Allah SWT. The practice of Sufism exemplified by Sufis generally teaches religious values ​​that produce noble moral behavior. Noble morals provide hope for the formation of an advanced civilization and do not ignore the divine values ​​that are always present in human hearts and lives. The aim of this research is to form a scientific concept regarding Sufism morals that is sustainable in the Islamic education process. The method in this research uses library study methods, reading content analysis, and descriptive analysis from various related sources. The results of the research found a concept that Sufism's morals produce noble morals towards Allah SWT, oneself, fellow humans and other living creatures in the universe through a process of self-purification and also approaching oneself to Allah SWT.